2021
DOI: 10.1111/epi.16972
|View full text |Cite
|
Sign up to set email alerts
|

Dietary medium chain triglycerides for management of epilepsy: New data from human, dog, and rodent studies

Abstract: Many studies show that glucose metabolism in epileptic brain areas can be impaired. Energy is crucial to maintain normal brain function, including ion and neurotransmitter balances. Energy deficits can lead to disruption of ion gradients, which can trigger neuronal depolarization and generation of seizures. Thus, perturbed metabolic processing of glucose in epileptogenic brain areas indicates a specific nutritional need for people and animals with epilepsy, as they are likely to benefit from auxiliary brain fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 148 publications
(365 reference statements)
0
31
0
4
Order By: Relevance
“…Participants from small animal primary care were more likely to recommend medium chain triglyceride supplements than those from mixed primary care practice. There is some evidence to support the use of medium chain triglycerides as a dietary supplement in drug resistant cases of canine IE (35)(36)(37)(38). There was a small decrease in seizure frequency of some dogs in a recent randomized controlled trial (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants from small animal primary care were more likely to recommend medium chain triglyceride supplements than those from mixed primary care practice. There is some evidence to support the use of medium chain triglycerides as a dietary supplement in drug resistant cases of canine IE (35)(36)(37)(38). There was a small decrease in seizure frequency of some dogs in a recent randomized controlled trial (37).…”
Section: Discussionmentioning
confidence: 99%
“…While dietary manipulation is commonplace by owners of dogs with IE (two thirds of owners changed the diet following IE diagnosis in one study (37) it is important that dogs with IE are fed a high-quality diet due to the long-term nature of management (37)(38)(39). A low-calorie diet is often necessary to maintain a healthy body weight in dogs with IE and long-term ASD treatment (38). Medium chain triglyceride oils may be high in fat and powders may be high in carbohydrates.…”
Section: Discussionmentioning
confidence: 99%
“…These triglycerides have been suggested for companion animals with lipid digestion problems and poor physical condition. Furthermore, Han et al [ 4 ] recently indicated medium-chain triglycerides as an auxiliary treatment for humans, rodents, and dogs with epilepsy. Indeed, these triglycerides provide additional energy in the central nervous system by compensating for the lack of energy due to current antiepileptic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…This supports its more frequent use in small animal nutrition. As MCT oil has been shown to be a useful adjunct in the nutritional management of a number of different conditions in dogs, including epilepsy [14,31] and cognitive dysfunction [17,32], MCT is still a promising nutritive component and should be further explored for its effects on other diseases in companion animals.…”
Section: Discussionmentioning
confidence: 99%